Pengaruh Pemberian Silase Pakan Komplit dari Berbagai Hijauan dengan Penambahan Konsentrat Mengandung ZnSO4 dan Zn-Cu Isoleusinat terhadap Fermentasi Rumen (pH, VFA dan NH3) pada Kambing Kacang - Jemiman, Maria Asri Anita; Oematan, Gustaf; Lestari, Gusti Ayu Y.; Kleden, Markus Miten (Animal Agricultura, 2025)
This study aims to determine the effect of providing complete feed silage from various types of forage with the addition of concentrate containing ZnSO4 and Zn-Cu isoleucinate on rumen fermentability (pH, VFA, and NH3) in Peanut Goats. The method used is an experimental approach with a Latin square design (RBSL), consisting of 4 treatments in 4 periods as replications, resulting in 16 experimental units. The treatments applied were silage based on Kume grass, Chromolaena odorata, sorghum, and Odot grass, each with 20% concentrate. The results of the analysis showed that the administration of 20% concentrate had no significant effect on pH (P>0.05), but had a very significant effect on VFA and NH3 concentrations (P<0.01). It can be concluded that feeding silage based on these forages does not affect pH, but increases VFA and NH3 concentrations.